Optimization of Colon Specific Drug Delivery System for Ornidazole using modified gum (International Journal of Pharmaceutical Sciences and Drug Research, 2021)
The present study aimed to optimize a colon-specific formulation of ornidazole for the treatment of Crohn's disease and intestinal amoebiasis. Firstly carboxymethyl xanthan gum was prepared from xanthan gum reacting with monochloroacetic acid in alkaline conditions using the Williamson synthesis method. Fourier transform infrared spectrophotometer (FTIR) spectroscopy confirmed the formation of carboxymethyl xanthan gum. The differential scanning calorimetry (DSC) revealed the crystalline nature of carboxymethyl xanthan gum. A 32 full factorial design was used for optimization. The independent variables employed were the amount of Carboxymethyl Xanthan gum and the amount of hydroxy propyl methyl cellulose (HPMC), each at three levels. Drug release studies were carried out in various media [pH 1.2, 7.4, and 6.8]. The optimized formulation consisting of Carboxymethyl Xanthan gum (66 %) and HPMC (22%) released a small fraction of drug at pH 1.2 and pH 7.4, whereas significant drug release was observed at pH 6.8. The results of the study established Carboxymethyl Xanthan gum compression coated tablet to be a promising system for the colon-specific delivery of ornidazole to treat active Crohn's disease and intestinal amoebiasis.